2018
DOI: 10.1248/bpb.b17-00723
|View full text |Cite
|
Sign up to set email alerts
|

An Aliphatic Ester Diisopropyl Sebacate Exhibited an Adjuvant Effect on Fluorescein Isothiocyanate-Induced Contact Hypersensitivity Mouse Models

Abstract: Alternative plasticizers have become more popular due to health concerns about phthalate esters. We demonstrated that phthalate esters enhanced skin sensitization to fluorescein isothiocyanate (FITC) in mouse contact hypersensitivity models. Alternative plasticizers have not been well studied as to their effect on the immune system. We previously found that diisopropyl adipate (DIPA), an aliphatic dicarboxylic acid ester, enhanced skin sensitization to FITC. Sebacate esters are also widely used as alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…17) However, diisopropyl adipate (DIPA; an alternative plasticizer) was found to induce only marginal IL-4 but abundant IFN-γ production by draining lymph nodes in BALB/c mice. 12) In the present study, DBP was confirmed to augment both IL-4 and IFN-γ production (Fig. 5).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…17) However, diisopropyl adipate (DIPA; an alternative plasticizer) was found to induce only marginal IL-4 but abundant IFN-γ production by draining lymph nodes in BALB/c mice. 12) In the present study, DBP was confirmed to augment both IL-4 and IFN-γ production (Fig. 5).…”
Section: Discussionsupporting
confidence: 75%
“…TRPA1 Activation in Vitro TRPA1-CHO cells were labeled with a calcium ion-sensitive fluorescent probe, Fluo 4-AM After automatic addition of a test sample (prepared in DMSO) in the presence or absence of a TRPA1 antagonist, HC-030031, the intracellular Ca 2+ level was measured over time with a fluorometric imaging plate reader, FLEXstation II (Molecular Devices, Sunnyvale, CA, U.S.A.) at 37°C as described previously. [12][13][14] The maximal Ca 2+ level was determined using 5 μM ionomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations